Exploring the use of games in palliative care: A scoping review - Lourenço, Marisa (2023)
Objective There has been increasing recognition of the potential of games in health; however, knowledge of their application in palliative care is lacking. Therefore, this study aimed to identify and map the available evidence on the use of games in palliative care, analyzing how research has been conducted on this topic and identifying gaps in knowledge. Method A scoping review was carried out. The literature search was conducted using the respective descriptors and search syntax appropriate to each of the databases searched. The review included all study types with no time limits. Results Of the 685 articles initially identified, 53 were included for final analysis. Several different game types were identified, with the majority of studies using role-play (n = 29) and card games (n = 17). The games analyzed were essentially aimed at empowering patients (n = 14), and in some cases, extended to families or caregivers, as well as to medical and nursing students. The analysis of the articles in this review resulted in two major themes: Role-playing for training in palliative care and card games to discuss end-of-life care. Significance of results Games allow space for the expression of emotions and promote creativity. They can be applied both in a training context, to enable health professionals to develop essential skills in palliative care, and for patients, families, and caregivers, allowing them to talk about serious things while playing.